2005
DOI: 10.1634/stemcells.2004-0317
|View full text |Cite
|
Sign up to set email alerts
|

CD133‐Positive Hematopoietic Stem Cell “Stemness” Genes Contain Many Genes Mutated or Abnormally Expressed in Leukemia

Abstract: Affymetrix human Hu133A oligonucleotide arrays were used to study the expression profile of CD133 + cord blood (CB) and peripheral blood (PB) using CD133 cell-surface marker. An unsupervised hierarchical clustering of 14,025 valid probe sets showed a clear distinction between the CD133 + cells representing the hematopoietic stem cell (HSC) population and CD133-differentiated cells. Two hundred forty-four genes were found to be upregulated by at least twofold in the CD133-positive cells of both CB and PB compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 45 publications
3
67
0
Order By: Relevance
“…Low expression of CD133 glycoprotein is associated with a more mature, proliferative cell fraction. 35 We also found a decreased expression of the genes encoding for L-selectin and CD53 in the HSC subset of CML patients (Table 1). These molecules seem to segregate asymmetrically in HSC according to the model of asymmetric cell division and characterize daughter cells that maintain stem-cell fate.…”
Section: The Hsc Subset Of Patients With CML Shows Impaired Migratorymentioning
confidence: 57%
“…Low expression of CD133 glycoprotein is associated with a more mature, proliferative cell fraction. 35 We also found a decreased expression of the genes encoding for L-selectin and CD53 in the HSC subset of CML patients (Table 1). These molecules seem to segregate asymmetrically in HSC according to the model of asymmetric cell division and characterize daughter cells that maintain stem-cell fate.…”
Section: The Hsc Subset Of Patients With CML Shows Impaired Migratorymentioning
confidence: 57%
“…Recently, oligonucleotide microarrays were used for the gene expression profiling of untreated CD133 + HSCs (CD133 + vs CD133 -) [33,34]. Both studies used the same Figure 6 Comparison mapping of genes expressed in erythroid and myeloid development and differentiation to biological processes.…”
Section: Discussionmentioning
confidence: 99%
“…npg procedures for enrichment of CD133 + cells, purification of RNA, amplification and labeling of RNA probes, and almost the same oligonucleotide microarrays (HG-U133A from Affymetrix), GeneChip scanners, and GeneChip operating software for data analyses. One study identified 690 differentially expressed genes and another identified 584 differentially expressed genes; however, some were inconsistent between these two studies [33,34]. Here, we analyzed the expression patterns of gene, protein and cell surface antigen, and the biological process of the related genes in erythroid and myeloid differentiation and switching of CD133 + HSCs in response to EPO and G-CSF.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it occurred at the PROM1 (prominin-1/CD133) gene (Fig. 1B), which encodes a defining antigen of hematopoietic stem cells and is purported to play a role in asymmetric cell divisions in adult stem cells (Wagner et al 2004;Toren et al 2005), and HOXA7, HOXA9, HOXA10 ( Fig. 2A), whose overexpression are hallmarks of ALLs carrying the t(4;11) chromosome translocation (Rozovskaia et al 2001(Rozovskaia et al , 2003Armstrong et al 2002;Yeoh et al 2002;Ferrando et al 2003).…”
Section: Identification Of Mll-af4-occupied Regions Of the Genome In mentioning
confidence: 99%